1997
DOI: 10.1016/s0735-1097(97)00076-4
|View full text |Cite
|
Sign up to set email alerts
|

Growth Factors Released Into the Coronary Circulation After Vascular Injury Promote Proliferation of Human Vascular Smooth Muscle Cells in Culture

Abstract: The change in plasma PDGF level is consistent with first-phase release of PDGF after vascular injury. The increase in mitogenicity of serum suggests that PDGF and bFGF are biologically active.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 20 publications
0
15
1
Order By: Relevance
“…Inhibition of cell proliferation, together with other well-documented effects of ®sh oil decreasing platelet aggregation (Mori et al, 1997), blood pressure (Morris et al, 1993) and modulating blood lipids (Connor et al, 1993), may contribute to the reported reduction in restenosis. Given that growth factor activity is higher following angioplasty (Caplice et al, 1997), it is possible that ®sh oil exerts lowering effects only in pathological states where growth factor levels are elevated. This may explain our observation of no signi®cant effect of ®sh oil on serum growth factor activity in apparently healthy individuals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibition of cell proliferation, together with other well-documented effects of ®sh oil decreasing platelet aggregation (Mori et al, 1997), blood pressure (Morris et al, 1993) and modulating blood lipids (Connor et al, 1993), may contribute to the reported reduction in restenosis. Given that growth factor activity is higher following angioplasty (Caplice et al, 1997), it is possible that ®sh oil exerts lowering effects only in pathological states where growth factor levels are elevated. This may explain our observation of no signi®cant effect of ®sh oil on serum growth factor activity in apparently healthy individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Platelet-derived growth factor (PDGF) expression is elevated in human atherosclerotic plaques compared with normal arteries, and increased plasma concentrations of PDGF have been reported in patients with diagnosed vascular disease (Wallace et al, 1998;Nilsson et al, 1986). Total mitogenic activity of serum for smooth muscle cells is elevated in individuals at risk of developing the clinical symptoms of IHD (Koschinsky et al, 1987) and also in acute studies of patients undergoing coronary angioplasty (Caplice et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Several serum-derived growth factors are known to be upregulated locally and released in atherosclerosis [22][23][24] and after coronary angioplasty in human subjects. 25 It is possible that growth factors within the vessel wall might locally regulate TFPI synthesis and secretion. Future studies will need to assess regulation of TFPI in vascular disease states where TF/factor VII activation plays a major role in thrombosis formation.…”
Section: Discussionmentioning
confidence: 99%
“…1 Numerous growth factors and mitogenic autocoids that could accelerate new tissue formation and development of the restenotic lesion have been found at the site of injury. 2,3 Signal transduction by these agents involves the mitogen-activated protein kinase (MAPK) pathway, and p21 rasdependent activation of p42/p44 MAPK has been demonstrated in vivo in a porcine model of balloon injury early after angioplasty. 4 Moreover, the local delivery of H-ras dominant negative mutant (N17 and L61, S186) plasmid constructs 5 and adenovirus-mediated transfer of dominant negative H-ras 6 have both been shown to significantly reduce neointima formation in the rat carotid artery.…”
mentioning
confidence: 99%